LEGAL AND PRACTICAL APPROACHES TO THE SUSTAINABLE USE OF RESORT NATURAL AREAS IN A GREEN ECONOMY - Alloberdiyeva Durdona Oktamjon qizi (European Science Publishing, 2025)
This article examines the potential of applying the green economy concept to promote regional development in the resort natural areas of Uzbekistan. It highlights how the integration of green technologies can contribute to maintaining ecological balance, developing sustainable infrastructure, and ensuring the efficient use of natural resources. The paper also analyzes the current legal and regulatory framework governing resort territories and identifies key areas for its improvement. Based on international practices and national priorities, the article provides recommendations aimed at enhancing environmental sustainability and supporting long-term socio-economic growth in these ecologically sensitive regions.
Keywords: Resort natural areas, green economy, sustainable development, natural resources, environmental safety, eco-tourism.